156 Could a Cohort of Patients be Listed Directly from Video Clinic to Surgery with Assessment on Day of Surgery? The Implementation of Video Clinic in Surgical Patients During the COVID-19 Lockdown. (12th October 2021) - Gendia, A; Al-Ardah, M; Jones, R; Korambayil, S; Clark, J; Clarke, M; Finlay, I; Peyser, P; Cota, A
Abstract: Aim: To report the feasibly and the safety of utilizing video Clinic during the 2020 pandemic in scheduling a cohort of patients to laparoscopic cholecystectomy (LC) without the need of face-to-face assessment. Method: A retrospective audit from May to October 2020 was conducted on patients with symptomatic biliary colic disease and selected low risk demographics who were vetted and scheduled for laparoscopic cholecystectomy through video clinic under one of the general surgeons (AC) in a large district hospital. All patients were given the option to have their face-to-face assessment on the day of surgery and if there would be any concerning signs, they would be postponed or investigated if required. Results: 33 patients agreed on the proposed option and were scheduled to LC based on virtual assessment, mean age of 42(±13) years old and 26(79%) were females. 16 (49%) patients had their surgery with average waiting time of 2.1(±1) months and mean BMI of 29.9(±7). 17 (51%) patients are pending future surgery dates. there was no cancellation based on surgery day assessment and or unexpected events intraoperatively. Conclusions: As virtual clinics played a major role in providing healthcare services during the global pandemic, scheduling patients to surgery without face-to-face assessment was applicable and safe in selected demographics. This could have the potential of reducing waiting time, travelling costs and hospital visits. Moreover, communications with patients regarding the proposed same day assessment played a vital role in reaching a mutual agreement.